The Effect of TPACK-Based Instructional Design on Science Learning Activity and Achievement: A Quasi-Experimental Study in Primary Education - Fisri Yeni; Darmansyah; Abna Hidayati; Ramalis Hakim (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the low level of active learning and inconsistent science achievement among primary school students. It aims to examine the effect of Technological Pedagogical and Content Knowledge (TPACK)-based instructional design on students’ learning activity and science performance. A quasi-experimental method with a nonequivalent posttest-only control group design was employed involving two classes: one taught using a TPACK-based approach and another using conventional instruction. Learning activity was measured through observation checklists and structured questionnaires, while science achievement was assessed through a multiple-choice test. Data were analyzed using descriptive statistics and an independent samples t-test. The results show that students in the TPACK group demonstrated notably higher levels of learning activity across visual, mental, and emotional dimensions compared to the control group. Their activity level was categorized as good, whereas the control group remained fairly good. Science test outcomes also revealed higher mean scores and lower score variance in the TPACK group. Statistical analysis confirmed significant differences between groups in both learning activity and science achievement. The study concludes that TPACK-based instructional design effectively integrates technology, pedagogy, and content to promote active engagement and enhance science learning outcomes in primary education.